Efektivitas dan Efisiensi Sistem Informasi Inventory pada CV. Ribut Snack - Adhi Wibowo; Lynawati Lynawati; Rosalina Yani Widiastuti; Antonius Ronny Lie Jaya (Jurnal HUMMANSI (Humaniora, Manajemen, Akuntansi), 2021)
CV. Ribut Snack Purwokerto is a trading company engaged in the distribution of special goods for snacks and snacks. Problems that often occur in CV. Ribut Snack Purwokerto is in managing inventory of goods. All of these activities are still carried out manually and the receipt of incoming and outgoing goods is still not well controlled, it can be seen that there is still data on goods that do not match the stock records. Therefore, the authors want to provide solutions to CV. Ribut Snack Purwokerto by creating a web-based application to manage inventory data using the FIFO (First In First Out) method. With this inventory information system, it is hoped that the inventory management of goods will be more effective and efficient.